Negotiations and bargaining: techniques - Craver, Charles B. (Henry Stewart Talks, 2011)
Common negotiating techniques, How to employ, How to recognize, How to counter, Consistent with own Style, Consistent with opposing side's style, Consistent with particular circumstances
Reviewed at 2020/07/30